THE ROLE OF GREEN FINANCING IN SUPPORTING SUSTAINABLE BUSINESS FOR MSMES IN TUNAS AUR VILLAGE, INDRALAYA DISTRICT, OGAN ILIR REGENCY - Hidayat, Ariodillah; Liliana, Liliana; Pertiwi, Rasyida; Yunisvita, Yunisvita; Andaiyani, Sri; Nida, Rahma; Butra Aini, Halia; Nopri Yarsyah, Waldi; Shodrokova, Xenaneira (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in the economy, contributing significantly to economic growth and job creation. However, MSMEs often face challenges, particularly in terms of limited access to financial resources needed for innovation and growth. Meanwhile, sustainability and environmental protection are increasingly becoming a global concern, encouraging the role of green financing as a solution to encourage environmentally friendly businesses. This research focused on Tunas Aur Village, Ogan Ilir Regency, involving 20 MSME participants. Through literacy and training activities, participants are given an in-depth understanding of the importance of green financing, with an approach involving lectures, discussions, and experiential learning using peer to peer lending applications, crowdfunding, and digital wallets. A total of 20 MSME participants in Tunas Aur Village illustrated that green financing literacy and training can create positive understanding and motivation for MSME actors in adopting sustainable business practices. In conclusion, this activity succeeded in increasing the understanding and interest of MSME participants in green financing, opening up potential for similar developments in the future, and providing valuable insights for improving MSME business sustainability through the application of green financing.